Optimized Biodiesel Production from Waste Cooking Oil Using Nickel (II) Nitrate Doped Chicken Manure as Catalyst - Obahiagbon, Kessington; Ahonkhai, David Ohimai (European Journal of Applied Sciences, 2023)
In this study, chicken manure was doped with nickel (ii) nitrate to produce catalyst for the synthesis of biodiesel from waste cooking oil. Characterization of the catalyst was achieved using Brunauer-Emmett and Teller (BET) analysis, fourier transform infrared spectroscopy (FTIR), scanning electron microscope and energy dispersive X-ray (SEM-EDX), and X-ray fluorescence (XRF). Box-Behnken design (BBD) was used in designing the experiments. The influence of various parameters including reaction temperature, time, methanol/oil ratio and catalyst loading were investigated. The catalysts characterization revealed the presence of high surface area (314.443m2/g) and pore size (2.123nm) and also metallic oxides such as silicon, aluminum and magnesium. Optimum biodiesel yield of 99.4026% was achieved at a temperature of 69.81℃, reaction time of 60 minutes with a methanol/oil ratio of 6:1 and catalyst loading of 1wt.%. This study confirms that chicken manure doped with nickel (ii) nitrate could be used as a heterogeneous solid catalyst for the biodiesel synthesis from waste cooking oil.